Dual‐Responsive Soft Actuators with Integrated Sensing Function Based on 1T‐MoS2 Composite. (5th May 2021) - Ji, Qixiao; Jing, Zhuang; Shen, Jinjie; Hu, Ying; Chang, Longfei; Lu, Luhua; Liu, Muye; Liu, Jiaqin; Wu, Yucheng
Abstract : Developing a multiresponsive and multifunctional soft actuator that can output mechanical deformation is crucial to the fields of soft robotics and wearable devices. Herein, a 2D metallic molybdenum disulfide (MoS2 )‐based soft actuator with dual‐response and self‐sensing function is designed and fabricated. By using the outstanding photothermal property of 1T phase MoS2, good electrical property and network structure of carbon nanotubes (CNTs), hygroscopic expansion of paper, and thermal expansion of polyimide (PI), the MoS2 ‐based actuator can respond to external voltage and light stimulation and produce rapid and large bending deformation. In addition, the actuator can be used as a flexible strain sensor to realize real‐time sensing of bending deformation by using piezoresistive property of the MoS2 –CNT composite film. Based on this soft actuator, a flexible mechanical gripper that can manipulate soft objects with irregular shape and intelligent wearable gloves that can automatically close to block the light irradiation are made. Furthermore, combined with the sensing feature of this MoS2 ‐based actuator, the gripper with integrated sensing function is also developed. These results indicate the great prospect of the MoS2 ‐based actuator in intelligent soft mechanical devices, robots, and wearable systems. Abstract : A dual‐responsive MoS2 ‐based soft actuator is fabricated, which not only shows good electrical/optical‐induced actuation with large deformation, but also exhibits strain sensing function. Based on these actuators, a flexible mechanical gripper for manipulation of the objects is constructed. Meanwhile, the mechanical gripper can also realize the integrated sensing of its own light‐induced grasping process, revealing its great application potential.